Considering Comparison: A Method for Religious Studies, by Oliver Freiberger. (10th February 2021) - Appleton, Naomi
Abstract : Considering Comparison: A Method for Religious Studies, by Oliver Freiberger. New York: Oxford University Press, 2019. 256 pp., £64 (hb). ISBN 978-0-19996-500-7.